2021
DOI: 10.3390/jpm11050413
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic Inflammation Response Score for Prognostic Prediction of Breast Cancer Patients Undergoing Surgery

Abstract: Background: Systemic inflammatory response is related to the occurrence, progression, and prognosis of cancers. In this research, a novel systemic inflammation response score (SIRS) was calculated, and its prognostic value for postoperative stage I-III breast cancer (BC) patients was analyzed. Methods: 1583 BC patients were included in this research. Patients were randomly divided into a training cohort (n = 1187) and validation cohort (n = 396). SIRS was established in the training cohort based on independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Wang, Chen, et al, 2021;Y. Wang, Xi, et al, 2021;Zhang et al, 2021). In 2020, we demonstrated that both the SII and the high-sensitivity modified Glasgow prognostic score (Hs-mGPS)…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 85%
See 1 more Smart Citation
“…Wang, Chen, et al, 2021;Y. Wang, Xi, et al, 2021;Zhang et al, 2021). In 2020, we demonstrated that both the SII and the high-sensitivity modified Glasgow prognostic score (Hs-mGPS)…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 85%
“…Inflammatory‐nutritional biomarkers impact the local tumor microenvironment, contribute to cancer progression, and predict the survival of patients with gastric cancer, rectal cancer, breast cancer, etc. (Farajzadeh Valilou et al, 2018; Hajizadeh et al, 2021; Ham & Moon, 2013; S. Li et al, 2021; Z. Li et al, 2020; Pang et al, 2021; N. Wang, Chen, et al, 2021; Y. Wang, Xi, et al, 2021; Zhang et al, 2021). In 2020, we demonstrated that both the SII and the high‐sensitivity modified Glasgow prognostic score (Hs‐mGPS) were independent predictive indicators of OS for R0‐resected STS (Hou et al, 2020), providing evidence for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports described an interesting association between PET uptake and different biomarkers of inflammation (NLR, PLR, SIRS) (29)(30)(31)(32), noting that patients with high SUVmax and Disease-free survival (A) and overall survival (B) according to pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports described an interesting association between PET uptake and different biomarkers of inflammation (NLR, PLR, SIRS) ( 29 32 ), noting that patients with high SUVmax and low NLR (indicating a status of immune system activation) had lower recurrent disease after surgery ( 30 ). In the present study, however, we did not find any correlation between PET parameters and systemic biomarkers of inflammation.…”
Section: Discussionmentioning
confidence: 99%